Methylphenidate Dose-Dependently Affects Aggression and Improves Fear Extinction and Anxiety in BALB/cJ Mice - Jager, Amanda; Kanters, Doranda; Geers, Femke; Buitelaar, Jan K.; Kozicz, Tamas; Glennon, Jeffrey C. (Frontiers in Psychiatry, 2019)
Overt aggression, increased anxiety and dysfunctional fear processing are often observed in individuals with conduct disorder (CD) and attention-deficit hyperactivity disorder (ADHD). Methylphenidate (MPH), a psychostimulant increasing dopamine and noradrenaline tone, is effective in reducing aggression in both CD and ADHD individuals. However, it is unclear to which extent these effects of MPH are dose-dependent. Here, the effects of acute intraperitoneal MPH (3 and 10 mg/kg) on aggression, anxiety, social behavior and fear extinction were investigated in BALB/cJ mice. Previous studies in BALB/cJ mice have revealed high levels of aggression and anxiety that are associated with reduced top-down cortical control. Administration of 3 mg/kg MPH prolonged the attack latency and prevented escalation of aggression over time compared to vehicle treated mice, while 10 mg/kg MPH increased number of bites and attacks. In addition, 3 mg/kg MPH decreased social interaction slightly. A strong anxiolytic effect was found after administration of both the 3 mg/kg and 10 mg/kg doses in the elevated plus maze and the open field test. In addition, while vehicle-treated BALB/cJ animals showed intact freezing, both doses of MPH decreased freezing to the unconditioned stimulus in a fear-conditioning paradigm. A long-lasting effect on fear extinction was visible after treatment with the 10 mg/kg dose. The data support a role for MPH in the regulation of anxiety, fear processing and aggression in BALB/cJ mice, with the latter effect in a dose-dependent manner. The findings provide a further context for examining the effects of MPH in clinical disorders as ADHD and CD.